(untitled) (The Research of Medical Science Review, 2025)
Dementia is a common but often overlooked complication in Parkinson’s disease (PD), significantly impacting patients' quality of life and daily functioning. The objective of this study was to determine frequency of dementia in patients with Parkinson Disease. This cross-sectional study, conducted over six months at the Neurology OPD and Ward of CMC Hospital Larkana, aimed to determine the frequency and associated risk factors of dementia among 196 patients aged 40–60 years with PD. Using standard cognitive assessments, the study found that 50.5% of patients exhibited signs of dementia. The condition was significantly more prevalent among males (60%), individuals aged ≥45 years (64.8%), and those with a disease duration of 10 months or more (59.4%). These findings highlight older age, male gender, and longer disease duration as key risk factors. Given the high prevalence, early detection and intervention strategies are essential to manage cognitive decline in PD patients, particularly in settings like Pakistan where such data has been scarce.